EZH2 as a therapeutic target for multiple myeloma and other haematological malignancies - Rosemarie Tremblay-LeMay; Nasrin Rastgoo; Maryam Pourabdollah; Hong Chang (BMC, 2018)
Abstract Enhancer of zeste homolog 2 (EZH2) is a histone methyltransferase that is of great interest in human cancer. It has been shown to have a dual nature, as it can act as a gene repressor or activator. Studies have highlighted the various roles of EZH2 in the pathophysiology of multiple myeloma (MM). It was also shown to have a role in the development of drug resistance in MM. There are several ongoing clinical trials of EZH2 inhibitors in haematological malignancies. Pre-clinical studies have provided a rationale for the therapeutic relevance of EZH2 inhibitors in MM. This paper reviews the evidence supporting the role of EZH2 in MM pathophysiology and drug resistance, with an emphasis on interactions between EZH2 and microRNAs, as well as the prognostic significance of EZH2 expression in MM. Furthermore, results from the pre-clinical studies of EZH2 inhibition in MM and currently available interim results from clinical trials of EZH2 inhibitors in haematological malignancies are presented. Preliminary data exploring anticipated mechanisms of resistance to EZH2 inhibitors are also reviewed. There is therefore strong evidence to support the relevance of targeting EZH2 for the treatment of MM.